Transparency vs. analysability: Re-examining the theories and degrees of semantic compositionality of idioms - Zovko Dinković, Irena (2013)
This paper questions the so-called idiom decomposition hypothesis (Gibbs & Nayak, 1989 ; Gibbs, et al. 1989), which presupposes that speakers have shared intuitions about the semantic compositionality of idioms, which in turn determines their syntactic flexibility. We have therefore conducted a study involving 150 participants, all native speakers of Croatian. Thirty familiar Croatian idioms, typically containing a verbal element and an object, were presented to the participants in three separate experiments. The first experiment was modelled after Gibbs & Nayak (1989) and Tabossi et al. (2008), and aimed at testing the speakers' intuitions about idiom compositionality. The participants were asked to distinguish between different degrees of idiom compositionality, namely normally decomposable (e.g. stisnuti zube ‘grit (clench) your teeth’), abnormally decomposable (e.g. piti krv na slamku komu ‘, literally “drink one’s blood with a straw”, meaning ‘get in (into) somebody’s hair’ or ‘make a nuisance of oneself’) and non-decomposable idioms (e.g. nisam (nisi itd.) veslo sisao ‘, literally “I didn’t suck on an oar”, meaning ‘I am nobody’s fool’, ‘I wasn’t born yesterday’). The second experiment tested the notion of syntactic flexibility and the appropriateness of various syntactic tests used to classify idioms as either flexible or non-flexible, and the third experiment was devised to test the recognition of idioms in particular contexts. The findings of the first experiment are consistent with those in Tabossi et al. (2008), namely that speakers' intuitions about the distinction between decomposable and non-decomposable idioms are not consistent. The results of the second experiment suggest that the degree of semantic analyzability is not directly connected to the idioms' syntactic flexibility, rather it is the internal structure of an idiom that governs its syntactic behaviour and renders some syntactic tests inapplicable (e.g. hypothetical meaning will preclude the use of past tense, unaccusative verbs will preclude passive forms). The initial results of the third experiment are consistent with the so-called configuration hypothesis (Tabossi et al. 2005), which claims that the figurative meaning of an idiom in discourse becomes recognizable when sufficient information is present to render it such. We expect our ongoing research to further corroborate these findings. This paper therefore aims to prove several points. First, that compositionality of idioms should be seen as a continuum (cf. Gibbs et al. 1989) but with transparency, not analysability, as the key factor. Second, that syntactic flexibility reflects the internal structure of idioms, and third, that the recognition of idioms in discourse is highly dependent on sufficient context. References: Gibbs, R. W., Jr., & Nayak, N. P. (1989). ‘Psycholinguistic studies on the syntactic behavior of idioms’. In: Cognitive Psychology, 21, 100-138. Gibbs, R. W., Jr., Nayak, N. P., Bolton, J. L., & Keppel, M. E. (1989). ‘Speakers’ assumptions about the lexical flexibility of idioms’. In: Memory & Cognition, 17, 58-68. Tabossi, P., Fanari, R., & Wolf, K. (2005). ‘Spoken idiom recognition: Meaning retrieval and word expectancy’. In: Journal of Psycholinguistic Research, 34, 465-495. Tabossi, P., Fanari, R., & Wolf, K. (2008). ‘Processing idiomatic expressions: Effects of semantic compositionality’. In: Journal of Experimental Psychology: Learning, Memory, & Cognition, 34, 313-327.